Practices in the Contextualization of the English Curriculum in the Public Secondary Schools - Pariscal, Dyna Rose P.; Gonzales-Aboy, Ivy (Technium Social Sciences Journal, 2022)
Abstract. Contextualizing instruction has been the growing consensus among educators. The United Nations Educational, Scientific, and Cultural Organization (UNESCO) has consistently called for educational reforms that reflect, and respect local contexts, traditions, and values based on the local needs and relevance to the learners. Likewise, the K to 12 curriculum framework highlights the cardinal importance of using context to shape the curriculum emphasizing that it shall be contextualized to allow schools to localize and indigenize for teachers to make the content relevant to the lives of learners considering their local, cultural knowledge, and even historical and biogeographical conditions in the planning, delivery, and overall implementation of the curriculum. Hence, it is necessary to investigate whether or not teachers in the Department of Education adhere to the contextualization mandate. This study aimed to describe the extent of practice in the contextualization of the English Curriculum in the degrees of localization and indigenization of a medium-sized schools division in Central Philippines. It also sought to find out if significant difference exists in the extent of contextualization practice in terms of sex, educational attainment, and length of teaching experience. Employing the descriptive-comparative design and a researcher-developed questionnaire, the study was conducted to 150 respondents. Results revealed that the extent of practice in the overall contextualization of the English curriculum and in terms of its degrees was very great except when respondents were grouped according to sex where male teachers’ extent of contextualization practice was only great. Furthermore, extent contextualization practice was strikingly lower in the degree of indigenization. Meanwhile, the difference in the extent of practice in the contextualization of the English curriculum was found to be statistically significant in terms of sex and length of service. In conclusion, English teachers’ extent of contextualization is influenced by their sex and length of service. Specifically, English teachers who are female and have more than ten years of teaching experience have better contextualization practices. The findings of this study formed the basis of the Contextualization of the English Curriculum Self-Check Tool designed for teachers to enable them and their schools to monitor and seriously contextualize the English Language Curriculum.